Physical activity, eating patterns, and insulin resistance in obesity - Erny Huriyati; Perdana Samekto Nugroho; Rina Susilowaty; Madarina Julia (Paediatrica Indonesiana, 2014)
Background Unhealthy eating patterns and physical inactivityare associated with obesity. Insulin resistance, an early sign of type2 diabetes mellitus, is common in obese individuals.Objective To assess for an association between physical activity andeating patterns to insulin resistance in obese female adolescents.Methods Subjects were 77 obese female adolescents aged 13-15years. Peripheral blood specimens were obtained for measurementsof fasting blood glucose, insulin, and the homeostatic modelassessment (HOMA) index. Subjects were considered to be in astate of insulin resistance for HOMA index 2::3. 16. Physical activityrecalls for 7 x 24h were performed to obtain information on subjects'energy expenditure, as well as intensity and duration of physicalactivity. Data on nutrients intake was also obtained using 7 x 24hfood recalls. Fat intake was categorized into saturated fatty acid(SAFA), unsaturated fatty acid (UNSAF A), monounsaturated fattyacid (MUFA), and polyunsaturated fatty acid (PUFA).Results Subjects spent most of their time on light activities, 23 .5(SD 2.0) hours/day. Those with insulin resistance spent slightly moretime doing light activities. Conversely, they spent less time in vigorousactivities, a mean difference of 4.96 (95%CI 0.61 to 9.31) minutes/day (P=o 0.01). Subjects who spent less than 1 minute/day in heavyactivities had higher odds for insulin resistance, (OR 3. 14; 95%CI1.20 to 8.50; P=o0.02). There were no relationships found betweennutrients intake, such as energy, protein, fats (SAFA, UNSAFA,MUFA, and PUFA), or carbohydrates, and insulin resistance.Conclusion In obese female adolescents, physical inactivityis associated with insulin resistance, while nutrients intakeis not associated with insulin resistance.